Fintech (Financial Technology) Dalam Sistem Pembayaran Non Tunai Di Perbankan Syariah (Studi Kasus Pada Bank Muamalat KCP Lamongan) - Faridah Niswatul Khoiroh; Eny Latifah (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to find about: (1) fintech service in the mobile banking-based non-cash payment system (Muamalat-DIN) at Bank Muamalat KCP Lamongan: (2) implementation of fintech in the mobile banking-based non-cash payment system (Muamalat-DIN) at Bank Muamalat KCP Lamongan. This study uses a descriptive qualitative research method. The results of this study are: (1) fintech services in the non-cash payment system in Muamalat-DIN are transfers, QRIS, credit top-ups, internet credit top-ups, electronic money top-ups, google play voucher codes, spotify premium, postpaid credit payments, PLN electricity, Telkom, cable TV, PDAM, IPB campus education payments, airplane tickets, ZISWAF, family takaful, BPJS employment, BPJS health, SAMSAT/SIGNAL, BPJPH, virtual accounts, multi payments, and hijrah pensions (DPLK); (2) the implementation of fintech at Bank Muamalat varies, there are Muamalat-DIN, phone banking, internet banking, MADINA, online share-e debit, and ATMs. The most popular Fintech at Bank Muamalat KCP Lamongan is Muamalat-DIN. In Muamalat-DIN, customers of Bank Muamalat KCP Lamongan often use services in the form of transfer, QRIS, credit top-ups and internet credit top-ups, electronic money top-ups, payment services such as PLN electricity, Telkom, PDAM, ZISWAF, BPJS for employment, BPJS for health, virtual accounts, and hijrah pension (DPLK). This fintech implementation has benefits for banks and customers, the benefit for Bank Muamalat KCP Lamongan is that it will have a wider reach, operational and marketing costs are more economical. And the benefits felt by customers are that transactions are easier, faster, accessible 24 hours because access is via a smartphone, and customers don't need to carry a lot of cash everywhere.